Effect of breakout phase on the stroke kinematics and coordinative swimming variables - Stosic, J.; Veiga, S.; Trinidad, A.; Dopsaj, M.; Navarro, E. (Sports Biomechanics, 2022)
The first complete upper and lower limbswimming cycle after the underwater segment of start and turns represents the breakout phase in competitive swimming. The aim of the present research was to examine the effect of the breakout movements on the stroking variables and coordinative patterns of competitive swimmers. Thirty-three national-level male swimmers performed 4 x 25 m maximal efforts (one of each stroke in random order) from a push start and were recorded by two sequential cameras in the sagittal plane. The average velocity, stroke length, and stroke frequency; the relative duration (%) of the stroke phases; and the inter-limb discrete relative phases were calculated using direct linear transformation algorithms for the breakout and free-swimming phases. In general terms, swimming velocity during breakout was faster (d 0.27 ± 0.04 m/s, p < 0.001, ES = 0.33) than free swimming (in all strokes but breaststroke), not because of a faster previous underwater kicking or a modified coordinative swimming pattern, but because of an increase in the stroke rate (d 4.68 ± 0.79 cycles/min, p < 0.001, ES = 0.36). These results indicate how swimmers manage the changing constraints during breakout from underwater to surface swimming.